2018
DOI: 10.1161/strokeaha.117.018859
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Risk of Ischemic Stroke in Young Men

Abstract: We found a strong dose-response relationship between the number of cigarettes smoked daily and ischemic stroke among young men. Although complete smoking cessation is the goal, even smoking fewer cigarettes may reduce the risk of ischemic stroke in young men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 9 publications
5
70
1
7
Order By: Relevance
“…Similar to previous studies [23][24][25], current smoking was found to be an independent risk factor associated with 1-year stroke recurrence after MIS. After stroke, persistent smoking increases the risk of stroke recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous studies [23][24][25], current smoking was found to be an independent risk factor associated with 1-year stroke recurrence after MIS. After stroke, persistent smoking increases the risk of stroke recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, over the last decade smoking is more frequently seen in young adults 54 55. A stronger dose-response relationship between smoking and the risk of ischaemic stroke is found for both men and women at young age compared with older adults 71 72. In stroke patients of all ages, the highest prevalence is reported in Europe (28.7%) and in Southeast Asia (24.8%), whereas the lowest prevalence was reported in Africa (13.9%).…”
Section: Vascular Risk Factors From Global Perspectivementioning
confidence: 99%
“…26,27 In addition, we found that smoking was associated with an increased risk of mortality among individuals with cerebrovascular disease, which was also consistent with the results of other studies. 28,29 Studies have reported that smoking can damage blood vessels by causing them to thicken and narrow, which may lead to stroke 30 and coronary heart disease. 31 However, we did not find a significant association between smoking and the risk of mortality among patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%